THE ROLE OF HEALTHY IDEOLOGIES IN MAINTAINING SOCIAL STABILITY (Scientific journal of the Fergana State University, 2024)
This article provides a socio-philosophical analysis of the issues of developing a healthy worldview, ideological immunity among young people in relation to various ideological threats that arise on a global scale. The article also discusses the issues of preparing the youth of our country to make far-sighted decisions by teaching them deep thinking. From a socio-philosophical point of view, the article analyzes the processes associated with the development of innovative technologies for introducing the national idea into the minds, hearts and inner world of young people in the context of globalization.